Estudo da atividade in vitro de componentes da dieta e de plantas medicinais do nordeste brasileiro sobre Helicobacter Pylori - Cândido, Cinthya Soares (2008)
Helicobacter pylori is a bacteria that infects about 50% of the world population constituting one of the principal risk factors for the development of gastric cancer. The emergence of this cancer type is associated to the presence of the bacteria and risk elements, such as the alimentary habits, the genetic predisposition and environmental factors. The present work had as objective evaluates the effect of components of the Northeastern diet (salt, vinegar, pepper and potato juice), extracts and essential oils on H. pylori growth. In the study a reference and a clinic strain were used. The chosen method for the accomplishment of the screening test was the inhibitory-zone testing and for determination of the Minimum Inhibitory Concentrations (MIC) it was used the agar dilution method as described by Clinical and Laboratory Standards Institute (CLSI). The strains were inoculated in appropriate culture medium containing different concentrations of the tested substances. The reading was determined macroscopically and the growth confirmed through the accomplishment of the microscopy by the Gram method and biochemical tests. It was verified that the salt did not inhibit the growth and morphology of H. pylori, however, it was able to influence the antimicrobial effect, in vitro. The vinegar and the pepper did not show antimicrobial activity. The potato juice was shown to promote the bacterial growth. The ethanolic extracts of Lippia alba Mill. N.E.B chemotypes I, II, III) and Egletes viscosa L. were active against the bacteria. The essential oils of Ocimum gratissimum L., Ocimum sp, Myracrodruom urundeuva All., L. alba Mill. N.E.B chemotypes I, II, III and E. viscosa L. were also active against H. pylori. The chemical characterization confirmed the majority constituents of the plants. H. pylori constitute, today, a vast research source in several areas. Related studies the transmission prevalence, resistance antimicrobial, new therapeutic alternatives and development of vaccines they are necessary and plenty promising.